PEMBELAJARAN REALISTIC MHATEMATICS EDUCATION (RME) DENGAN PENDIDIKAN KARAKTER UNTUK MENINGKATKAN LITERASI MATEMATIKA - Eva Monika Safitri Lubis; Fitriani Fitriani (DIRASATUL IBTIDAIYAH, 2022)
The results of the Program for International Students Assessment (PISA) state that the mathematical ability of students in Indonesia is ranked low when compared to students in other countries and in industrialized countries. Despite the fact that mathematics is known for its challenges, many students are less enthusiastic about the subject, but some students also enjoy math. Students in the classroom have a variety of characters, attitudes, and traits. To help children develop into good students, teachers must be able to understand and shape their character. Information on the RME learning model with character education and students' mathematical literacy skills at SDN 115492 Mampang is the objectives of this research. Surveys and various literature studies were use in the implementation of this research. Research findings reveal that students still struggle to relate their skills to various social problems, math problems, and apply mathematical concepts. The model used has not succeeded in stimulating mathematical literacy. In addition, teachers have not fully incorporated character education values into mathematics learning. The learning model (RME) can be used as a learning model that will improve character education and improve students' mathematical literacy while they are learning mathematics.Keywords: Learning, Realistic Mhatematics Education (RME).